Adhesives - Applications and Properties 2016
DOI: 10.5772/65605
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion in Restorative Dentistry

Abstract: Bonding agents play a crucial role in the effective sealing and retention of resin-based composite restorations, which have been increasingly placed and replaced by dentists in many countries around the world. In fact, direct adhesive restoration with composite resins has become the procedure of choice for the treatment of anterior and posterior teeth. However, long-term durability of those restorations may be compromised due to progressive loss of the integrity of adhesive interfaces. This means that no adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 115 publications
(292 reference statements)
2
6
0
1
Order By: Relevance
“…As it solubilize the mineral content of dentin (including the smear layer) to allow the adhesive monomers to infiltrate into the collagen network and replace the water between the collagen fibrils forming a hybrid layer, and in combination with the resin tags inside dentine tubules provides a wide surface for adhesion and allow for micromechanical interlocking. (23,24) Our results are in agreement with De Munck et al (2) results who stated that for both the interfacial fracture toughness and microtensile bond strength test, a general trend could be observed that multistep adhesives bonded more effectively than simplified one-step adhesives. This overall trend was also following the same trend as found in a recent meta-analysis on parameters involved in dentin bonding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As it solubilize the mineral content of dentin (including the smear layer) to allow the adhesive monomers to infiltrate into the collagen network and replace the water between the collagen fibrils forming a hybrid layer, and in combination with the resin tags inside dentine tubules provides a wide surface for adhesion and allow for micromechanical interlocking. (23,24) Our results are in agreement with De Munck et al (2) results who stated that for both the interfacial fracture toughness and microtensile bond strength test, a general trend could be observed that multistep adhesives bonded more effectively than simplified one-step adhesives. This overall trend was also following the same trend as found in a recent meta-analysis on parameters involved in dentin bonding.…”
Section: Discussionsupporting
confidence: 91%
“…This overall trend was also following the same trend as found in a recent meta-analysis on parameters involved in dentin bonding. (25) Our results are also supported by Alexandra et al (23) who stated that 3step total etch adhesive systems have been shown to perform well in both laboratory and clinical assays and are still seen as the gold standard among bonding systems. (26,27) Our results are also supported also by Ayres et al (28) results they declared that the fracture toughness values appeared to depend on both the adhesive and application mode as multi-mode adhesives performed more effectively in total etch mode than in self-etch mode.…”
Section: Discussionsupporting
confidence: 83%
“…To bypass this drawback an additional HBL is applied over the polymerized adhesive [ 49 , 50 ]. Previous reports have described its improved performance and degradation prevention of the resin–dentin bonds as a result of the increasing thickness and uniformity of the adhesive layer, as well as to reduce the fluid flow across the adhesive interface [ 51 , 52 ]. However, this method has not been tested with self-etch adhesive systems applied over CSC in order to evaluate the bond strength and interface structure between them.…”
Section: Discussionmentioning
confidence: 99%
“…In bonded restorations, microleakage is a significant element [ 1 ]. Complications of microleakage in dentistry include increased saliva and microorganisms’ penetration between the restoration and tooth, secondary caries, destruction and discoloration at the margins, pulp irritation, and postoperative sensitivity that might compromise the clinical durability of the treatment.…”
Section: Introductionmentioning
confidence: 99%